Effects of organic and inorganic selenium on selenium bioavailability, growth performance, antioxidant status and meat quality of a local beef cattle in China - Huang, Qi; Wang, Shuiping; Yang, Xin; Han, Xuefeng; Liu, Yong; Khan, Nazir Ahmad; Tan, Zhiliang (Frontiers in Veterinary Science, 2023)
Selenium (Se) is an essential nutrient with multiple health benefits to humans and animals. Cattle generally require dietary Se supplementation to meet their daily requirements. The two main forms of dietary Se in cattle are organic Se and inorganic Se. Data comparing the health and productivity effects of organic Se and inorganic Se on cattle are still insufficient, and it is necessary to conduct more research to evaluate the bioavailability, nutritional value, deposition, and body functions of Se sources in different breeds and physiological stages of cattle raised in areas with different Se levels. The objectives of this study were to determine the effects of organic and inorganic sources of Se on plasma biochemical indices, Se bioavailability, deposition in body tissues and organs, growth performance, antioxidant capacity and meat quality of beef cattle raised in Se-deficient areas. Fifteen Chinese Xiangzhong Black beef cattle with an average weight of 254.5 ± 8.85 kg were assigned to three dietary groups. The three groups were fed the same basal ration and supplemented with either an inorganic (sodium selenite (SS)), organic (selenomethionine (SM)), or Se-enriched yeast (SY)) source of Se (0.1 mg/kg dry matter) for 60 days. At the end of the experiment, three cattle from each group were randomly selected and slaughtered, and samples were collected from tissues and organs for analysis. The results revealed that growth performance, slaughter performance, Se content of tissues and organs, meat quality characteristics including chemical composition, pH45min, pH24h, drip loss, and cooking losses did not differ (P>0.05) due to supplementation of the different organic and inorganic sources of Se. SM and SY were more effective in increasing (P<0.05) immunoglobulin M (IgM) concentrations in the blood and reducing (P<0.05) malondialdehyde (MDA) content in the longissimus dorsi than SS. In conclusion, organic Se is more effective than inorganic Se in improving the immune and antioxidant capacity of Chinese Xiangzhong Black beef cattle.